Joint-tissue integrative analysis identifies high-risk genes for Parkinson’s disease - Wu, Ya-Shi; Zheng, Wen-Han; Liu, Tai-Hang; Sun, Yan; Xu, Yu-Ting; Shao, Li-Zhen; Cai, Qin-Yu; Tang, Ya Qin (Frontiers in Neuroscience, 2024)
The loss of dopaminergic neurons in the substantia nigra, along with the abnormal accumulation of synuclein proteins and neurotransmitters in Lewy bodies, constitutes the primary symptoms of Parkinson's disease (PD). Besides environmental factors, scholars are in the early stages of comprehending the genetic factors involved in the pathogenic mechanism of PD. Although genome-wide association studies (GWAS) have unveiled numerous genetic variants associated with PD, precisely pinpointing the causal variants remains challenging due to strong linkage disequilibrium (LD) among them. Addressing this issue, expression quantitative trait locus (eQTL) cohorts were employed in a transcriptome-wide association study (TWAS) to infer the genetic correlation between gene expression and a particular trait. In utilizing the TWAS theory alongside the enhanced Joint-Tissue Imputation (JTI) technique and Mendelian Randomization (MR) framework (MR-JTI), we identified a total of 159 PD-associated genes by amalgamating LD score, GTEx eQTL data, and GWAS summary statistic data from a substantial cohort. Subsequently, a Fisher's exact test was conducted on these PD-associated genes using 5152 differentially expressed genes sourced from 12 PD-related datasets. Ultimately, 29 highly credible PD-associated genes, including CTX1B, SCNA, and ARSA, were uncovered. Furthermore, GO and KEGG enrichment analyses indicated that these genes primarily function in tissue synthesis, regulation of neuron projection development, vesicle organization and transportation, as well as lysosomal impact. The potential PD-associated genes identified in this study not only offer fresh insights into the disease's pathophysiology but also suggest potential biomarkers for early disease detection.